(untitled) - Johnson, Mark (New York, 2003)
This book provides a practical "rules of thumb" approach to making accurate optical measurements with equipment commonly found in labs and companies. Considers the full chain of equipment: photodetectors, amplifiers, LED sources, electronic drives, basic optics, interference screens, and data acquisition systems How to make use of the simplest detector in every situation Noise reduction techniques Building in stability
Keywords: Optical detectors,Optoelectronic devices,Light,Ánh sáng,Máy dò quang,Thiết bị quang điện; Measurement,Phép đo